PRINCIPAL COMPONENT ANALYSIS OF MORPHOLOGICAL TRAITS OF ASSAM HILL GOAT IN EASTERN HIMALAYAN INDIA - G. Khargharia; G. Kadirvel; S. Kumar; S. Doley; P. K. Bharti; Mukut Das (Journal of Animal and Plant Sciences, 2015)
The present study aimed to investigate the type and function of the Assam Hill goat of Northeast India. A total of 67 female animals of 2 to 4 years of age were randomly selected to record body weight and 13 linear body measurements and 21 body indices. The body weight (BW), body length (BL), height at withers (HAW), rump height (RH), rump length (RL), rump width (RW), chest depth (CD), heart girth (HG), paunch girth (PG), cannon bone length (CL), cannon bone circumference (CC), sacral pelvic width (SPW), shoulder width (SW) and sternum height (SH) were estimated to be 24.86 ± 0.80 kg, 61.48 ± 0.57, 54.57 ± 0.57, 58.05 ± 0.59, 14.57 ± 0.23, 13.11 ± 0.27, 27.68 ± 0.45, 71.93 ± 0.99, 86.05 ± 1.77, 12.14 ± 0.17, 7.71 ± 0.10, 76.93 ± 1.34, 15.66 ± 0.24 and 26.89 ± 0.49 cm, respectively. The height slope (HS), length index (LI), body index (BI), pelvic index (IP), dactyl thorax index (DTI), body ratio (BR), Baron and Crevat (BC), compact index (CI), balance, area index (AI) and relative cannon thickness index were found to be 3.43 ±  0.29, 1.14 ± 0.02, 86.87 ± 0.85, 92.49 ±  2.54, 9.82 ±  0.38, 0.93 ± 0.01, 93.18 ±  2.86, 5.48 ±  0.23, 5.63 ±  0.23, 3355.13 ±  48.84 and 12.95 ± 0.14 respectively. The correlation coefficients were found to be highest between BW and BL (0.86) and lowest between RW and PG (-0.32). Principal component (PC) analysis after varimax rotation produced four PCs which showed 85.84 per cent of the total variation. The coefficient of determination (R2) value was found to be 0.74 when BL was included in the prediction model, but it increased to 0.87 when the other linear measurements viz. HG, RL, PG and SPW were included in the model. The inclusion of PCs to predict body weight of Assam Hill goat was found to be more precise. The study revealed that Assam Hill goat is elipometric, well adapted to the hilly terrain of Northeast India and suitable for meat production.
Keywords: Assam Hill goat; linear body measurements; body indices; regression; Principal component analysis